Male Football Comedy. A Reappraisal of Traditional, Declassed, Toxic Masculinity. Ted Lasso as an Improved Continuation of British Television Sports Series - Anna Tous Rovirosa (Historia y Comunicación Social)
This research focuses on UK television sports sit-coms (2002-2023), which we propose to name as 'male football comedy', and their depiction of declassed male characters in the so-called masculinity crisis. It investigates the causes of the comic portrayal of men in professional and personal failure, leading to toxic masculinity, in contrast to the cliché of the 'bossy woman'. The various productions portray class difference and, more specifically, the abyss between elite soccer and the working class. It is concluded that the subgenre and its somehow inherent toxic masculinity have been maintained, criticised and at the same time legitimised, and that US TV series Ted Lasso, belonging to the same subgenre, constitutes a conciliatory proposal for a better relationship between genders.